Effect of Number of Retrieved Lymph Nodes on Prognosis in FIGO Stage IA1-IIA2 Cervical Cancer Patients Treated With Primary Radical Surgery - Shan Jiang; Peng Jiang; Tingting Jiang; Yuan Tu; Jingni Zhang; Ning Li; Wei Kong; Yuzhen Huang; Rui Yuan (SAGE Journals, 2022)
Background:
The influence of the number of removed lymph nodes (RLNs) on patients with early-stage cervical cancer (ESCC) is still questionable. The objective of this study was to explore the prognostic value of RLNs on ESCC patients.
Methods:
A retrospective study was performed including all ESCC patients who underwent radical surgery from January 2016 to December 2018. Cox regression analysis was performed to verify the correlation between the number of RLNs and the prognosis (recurrence-free survival [RFS], disease-specific survival [DSS]) of ESCC. According to the guidelines, all the patients were divided into high-risk and non-high-risk groups. The optimal cut-off values of RLNs were determined by receiver operating characteristic curve analysis and Youden index and further the prognostic value of them was explored.
Results:
A total 1101 patients were enrolled. The number of RLNs was an independent prognostic influence factor of the prognosis of ESCC (P < .001 for RFS, P < .001 for DSS). The optimal cut-off values of RLNs (40 in the high-risk group and 23 in the non-high-risk group) were significantly associated with the prognosis of ESCC, in the high-risk group (P < .001 for RFS, P = .002 for DSS) and non-high-risk group (P < .001 for RFS, P < .001 for DSS), respectively.
Conclusions:
More extensive lymph node dissection (RLNs ⩾ 40) could benefit the high-risk ESCC patients. However, in the non-high-risk group, moderate lymph node dissection (RLNs ≈23) could also benefit them and may reduce the incidence of related complications. Those findings may help to determine the scope of lymph node dissection in ESCC patients before operation.
Keywords: Oncology and Carcinogenesis not elsewhere classified